Assessment of the incidence of pain in the immediate postpartum period: An observational study in the maternity ward of the Hospital Universitário do Oeste do Paraná (Research, Society and Development, 2025)
The immediate postpartum period, which occurs up to the 10th day after delivery, is marked by the gradual return of the woman's body to its pre-pregnancy state. Many women experience pain in the lower back, abdominal, perineal, and breast regions, associated with both vaginal and cesarean delivery. This study aimed to evaluate the incidence of pain in the immediate postpartum period, identifying the main pain sites reported by postpartum women and investigating the relationship between these discomforts and factors such as type of delivery, breastfeeding, and musculoskeletal pain. This is a cross-sectional observational study, carried out with women in the immediate postpartum period, from September to October 2024. A semi-structured questionnaire was used with questions about the participants' personal and obstetric data, in addition to questions related to the presence of pain. The study included 50 women, aged 17 to 41, 38% of whom were primigravidae and 62% primiparous. The majority (54%) underwent cesarean section. The most frequent pain occurred during the cesarean incision, followed by abdominal and perineal pain. For 55.8% of the women, the pain was moderate. Movement was indicated as an aggravating factor, while rest alleviated the symptoms. The study revealed that pain in the immediate postpartum period is common and affects quality of life, especially after a cesarean section. The importance of greater guidance during prenatal care regarding postpartum discomfort is highlighted. Techniques such as kinesiotherapy and TENS have proven effective in relieving pain and in functional recovery.